Penggunaan Pupuk Organik Cair Batang Pisang Untuk Tanaman Jagung Di Kelompok Tani Sumber Rezeki Di Mendalo Darat Di Kabupaten Muaro Jambi - Hasriati Nasution; Asmadi Saad; Yusfaneti (WIDA Publishing, 2022)
Sweet corn ( Zea mays saharata Sturt ) is a type of staple food that can replace rice. Sweet corn is the most widely cultivated after rice. Sweet corn can be processed directly boiled because it tastes quite sweet. The Sumber Rezeki farmer group is trying to plant sweet corn in addition to other vegetable crops because the extension agent will provide a method of making liquid fertilizer from banana stems after it is finished, it will be given to sweet corn plants planted on Ultisol soil type. The service carried out is in the form of material counseling and direct demonstrations in the field for 3 months in 2022 from a preliminary survey, determining a schedule and conducting outreach activities in the manufacture of liquid organic fertilizer from banana stem raw materials for long beans. The counseling was carried out in two stages, namely by providing material related to the use of compost for organic fertilizer for sweet corn plants. After that, it was continued by carrying out a direct demonstration in the field on how to apply liquid organic fertilizer from banana stems to long bean plants at the Sumber Rezeki farmer group. For the smooth implementation of service. So the Community Service Team provided the materials needed for counseling and demonstrations, namely banana stems to make liquid organic fertilizer, buckets with lids, sugar, EM 4 microorganisms, hoes, machetes and clean water. Previously, material duplication, photo props and preparation for consumption were also prepared during a demonstration in the use of liquid organic fertilizer from banana stems for sweet corn at the Sumber Sustenance farmer group in Mendalo Darat Village, Muaro Jambi Regency. The results after carrying out the counseling showed that farmers in the Sumber Rezeki Farmer group were very enthusiastic in listening and discussing and when making liquid organic fertilizer from banana stems and using it for corn plants in the field the farmers really understood. And after receiving this material counseling, it is hoped that the corn farmers in the Sumber Rezeki Farmer Group will be able to provide their own fertilizer for the sweet corn plants so that the yield of sweet corn will increase and can as income increase the income of the Sumber Rezeki farmer group.